The marketing of the small enterprise - Zajfertová, Alena (2009)
The purpose of this thesis is to analyse the marketing of a small enterprise, and it's position and importance on the market. It will also include an analysis of the informational and financial support of the EU. For the practical part there was chosen a small enterprise Nana Vogue, which is specialised in luxurious clothing.